Influence of the SME run Perkins 1104D-44TA engine on the power and torque as well as unitary and hourly fuel consumption - Łagowski, P.; Kurczyński, D.; Wcisło, G.; Pracuch, B.; Leśniak, A.; Tomyuk, V. (Lublin, 2018)
he article presents the results of tests determining the impact of using sunflower oil methyl esters on power and torque as well as unitary and hourly fuel consumption of the Perkins 1104D-44TA engine. Biofuels were produced in the Fuel and Energy Laboratory belonging to the Maopolskie Centrum Energii Odnawialnej (Małopolskie Center for Renewable Energy Sources), while analyzes of the selected fuel parameters were performed both in the above-mentioned laboratory and in the Liquid Biofuels Laboratory at the University of Agriculture in Krakow. Engine tests were carried out on the engine test stand at the Kielce University of Technology. During the tests, the engine worked according to the external speed characteristic. The results of the tests have shown that the engine supplied with the SME achieves slightly lower values of both power and torque than in the case of commercial fuel oil type Ekodiesel Ultra from the ORLEN S.A company. There was also an increase, especially in the case of higher unitary fuel consumption. Hourly fuel consumption was higher when supplied with SME in relation to the diesel fuel supply, although not as much as unitary consumption. The increase in SME consumption at the engine supply can be explained by the lower fuel value of SME, which contains oxygen in its structure.
Keywords: combustion engine; biofuels; methyl esters of sunflower oil; external speed characteristics